Post a New Question


posted by .

(a^6 x a^6)^k = (a^3)^(k+5)

Solve for k.
a. 3/2
b. 5/3
c. 2
d. 3
e. 5

I think when simplified its (a^12)^k = (a^3)^(k+5)
but i don't know how to get k from here. How do you solve for these kind of exponents?

  • Math -

    a^12 = (a^3)^4, so

    (a^3)^(4k) = (a^3)^(k+5), so
    4k = k+5
    k = 5/3

  • Math -

    Thank you so much :D

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question